Semantics Analysis of the Patriarchy’s System toward the Woman’s Silent Reflected in ‘The Patience Stone’ Novel - Ani Musafa'ah (STKIP PGRI SIDOARJO, 2019)
Patriarchy is one of the great problems for every women in the world, this problem finally is represented to a literary work, and one of it is Atiq Rahimi’s The Patience Stone. This study was done by the aim to describe the semantics meaning of the patriarchy’s system toward the woman’s silent. To solve it by analysis, it requires a method that is reading, collecting data, and interpreting the data examined in the descriptive qualitative design. As the result of this study, it was found the silent voice of the Woman that can be said that patriarchy system can grab the rights of women, and what things that the Woman can deliver is the silent voice, the voice that can be a feminist movement for every sympathy to it. It represents, it says in very smooth whispers that there are still inequality caused by patriarchy, and the Woman cannot do anything. Overall, there were 14 data found representing the patriarchy’s system faced by the woman as the main character in case of language meaning applied.